Determinant of escalating construction material costs in the post-pandemic period: contractor’s perspective - Azahar, Nuramira Farhana; Raja Muhammad Rooshdi, Raja Rafidah; Ismail, Noor Akmal Adillah; Marhani, Mohd Arif; Sahamir, Shaza Rina; Wan Azahar, Wan Nur Aifa; Mohd Yunus, Rihana (Universiti Teknologi Mara, 2025)
The COVID-19 pandemic emerged as the most talked-about topic of the year, damaging the economy, and upsetting the lives of many people and businesses across industries. Its effect, which varies by industry, was enormous in the construction industry, causing Malaysian construction projects to suffer the consequences of escalating material costs during the pandemic and post-pandemic period. This study aims to improve the effects of the escalating construction material costs by identifying the factors influencing the escalating construction material costs in construction projects from the contractor's perspective. This research was conducted using questionnaire surveys and distributed to Selangor Contractors Grade G6 and G7 registered with the Construction Industry Development Board (CIDB). Descriptive statistics and ranking analysis were used in data analysis. The finding showed nine (9) factors influencing the escalating construction material costs, transportation costs & fuel price increases, supply chain disruptions & material shortages, labour shortages, higher labour costs, demand increases, economic factors, tariff increases & trade policy changes, health & safety costs increase and Government policies & regulations. Thus, this study must be put into consideration, as it ultimately helps to enhance the construction industry's performance. Finally, construction professionals, industry, and the government will benefit